The complete chloroplast genome of Juniperus rigida (Cupressaceae) - Mingcheng Wang; Rui Li (Mitochondrial DNA. Part B. Resources, 2022)
The complete chloroplast (cp) genome of Juniperus rigida was assembled using Illumina short reads. The assembled plastome showed a circular structure with an overall size of 127,720 bp. Inverted repeat (IRs) regions were absent from the J. rigida cp genome. A total of 119 genes were predicted, including 82 protein-coding genes, 33 tRNA genes, and 4 rRNA genes. The overall GC content of J. rigida cp genome was 34.92%. Phylogenetic analysis among J. rigida and 19 other Cupressaceae species showed that J. rigida clustered together with J. formosana. The J. rigida cp genome presented in this study will provide useful genetic resource for further evolutionary studies of the genus Juniperus as well as Cupressaceae.